Husks of Zea mays as a potential source of biopolymers for food additives and materials' development. Issue 3 (March 2019) - Bernhardt, Dana C.; Ponce, Nora M.A.; Basanta, Maria F.; Stortz, Carlos A.; Rojas, Ana M.
Abstract: Maize husks, an agricultural and industrial residue generated in a large volume, were investigated as a potential source of useful biopolymers. Thus, their chemical composition was firstly studied, after which two biopolymer products were obtained and characterized. Maize husks were dried and milled, obtaining a 210 μm-main particle size powder (MHP). It contained carotenes (4 mg/100 g), and exhibited antioxidant capacity (≈195 mg ascorbic acid/100 g MHP) coming also from extractable coumaric and cinnamic acids-derivatives (14 mg/100 g). A 31% of the MPH was water-soluble at room temperature, mainly constituted by fructose, glucose, and sorbitol of mesophylls' intracellular origin. The water insoluble fiber (WIF, ≈70%), which showed antioxidant capacity (≈25–33 mg ascorbic acid/100 g WIF), was almost entirely constituted by the cell wall biopolymers or alcohol insoluble residue (AIR) of the MPH, mostly arabinoxylans (≈26%) crosslinked by ferulic residues (18.6 mg/100 g MPH), and cellulose (26%). Low levels of pectins (5.5%) and lignin (7%) were found. Hence, a 1.25%-sulfur nanocellulose (NCC) was directly obtained with sulfuric acid (−15 mV Zeta-potential; 147 °C onset of thermal-degradation) without the necessity of previous delignification. On the other hand, a water soluble arabinoxylan enriched fraction (AX-EF) with pseudoplastic behavior in water and sensibility to calcium ions (≈3 Pa⋅s initial Newtonian-viscosity) was isolated by alkaline hydrolysis of diferulate bridges. Despite a 56% of crystallinity, NCC showed the highest water absorption capacity when compared to that of the AX-EF and AIR. Maize husks constitute an important source of biopolymers for development of materials and food additives/ingredients with relevant hydration and antioxidant properties.